2018
DOI: 10.1038/s41396-018-0245-3
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral gene acquisition as the key to virulence potential in environmental Vibrio populations

Abstract: Diseases of marine animals caused by bacteria of the genus Vibrio are on the rise worldwide. Understanding the eco-evolutionary dynamics of these infectious agents is important for predicting and managing these diseases. Yet, compared to Vibrio infecting humans, knowledge of their role as animal pathogens is scarce. Here we ask how widespread is virulence among ecologically differentiated Vibrio populations, and what is the nature and frequency of virulence genes within these populations? We use a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 73 publications
0
51
0
Order By: Relevance
“…This strain was shown to be cytotoxic to hemocytes (16), but the mechanisms causing cytotoxicity remain unknown, and it remains unclear whether other strains belonging to V. tasmaniensis or to the Splendidus clade as a whole are also intracellular pathogens and cytotoxic to hemocytes. Within the Splendidus clade, virulence is an ancestral trait that has been lost in several species (12). The ancestrally acquired r5.7 gene, which encodes for an exported protein of unknown function, is necessary for virulence across the entire Splendidus clade (12,14).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…This strain was shown to be cytotoxic to hemocytes (16), but the mechanisms causing cytotoxicity remain unknown, and it remains unclear whether other strains belonging to V. tasmaniensis or to the Splendidus clade as a whole are also intracellular pathogens and cytotoxic to hemocytes. Within the Splendidus clade, virulence is an ancestral trait that has been lost in several species (12). The ancestrally acquired r5.7 gene, which encodes for an exported protein of unknown function, is necessary for virulence across the entire Splendidus clade (12,14).…”
Section: Significancementioning
confidence: 99%
“…For example, in oysters with Pacific oyster mortality syndrome, a Herpes virus was shown to cause immune suppression, enabling microbiome dysbiosis and proliferation of bacteria such as Vibrio crassostreae (10). This species and other closely related species of the Splendidus clade (e.g., Vibrio splendidus, Vibrio tasmaniensis, and Vibrio cyclitrophicus) have been repeatedly isolated from diseased oysters, and their virulence confirmed in experimental oyster infections (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Knowledge of their role as animal pathogens and their mechanisms of action in pathogenesis has been limited. Indeed, Bruto et al (2018) recently showed that, within the Splendidus clade, virulence represents an ancestral trait, but it has been lost from several populations. They identified two loci necessary for virulence and can now associate virulence in bivalves with one or many specific V. splendidus strains.…”
Section: Bacterial Profilesmentioning
confidence: 99%
“…Additionally, multiple known virulence genes of V. splendidus pathogens shown to be important for virulence of species were not signi cantly correlated with our pathogenicity results, including . This includes the exported protein of unknown function R5-7 (AXN33180.1) [14,64], present in 33 tested isolates, the MARTX toxin of V. splendidus (WP_108195411.1) [14], present in two tested isolates, and Type 6 Secretion Systems (T6SS) [14,15,66]. Apparent differences between previous results and ours may arise from minor, but important, differences in sequences of each locus, differences in methods applied for gene clustering, environmental conditions such as temperature, or divergent controls of transcription of conserved genes between pathogenic and non-pathogenic isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Within some species of Vibrio, there are well-de ned mechanisms for virulence. For instance, within the Splendidus clade of Vibrios, numerous virulence factors, including an exported protein of unknown function, gene r5.7 [13,14], species-speci c Type 6 Secretion System effectors [15], and the Multifunctional-Autoprocessing Repeats-in-Toxin (MARTX) cluster [14], have been shown to affect Paci c Oyster (Crassostrea gigas) adults and juveniles. The importance of a zinc metalloprotease has also been reported in several Vibrio oyster pathogens, including V. tasmaniensis [16], V. aestuarianus [17], and V. coralliilyticus [18].…”
Section: Introductionmentioning
confidence: 99%